State insurance mandates and racial and ethnic inequities in assisted reproductive technology utilization - Korkidakis, Ann; DeSantis, Carol; Kissin, Dmitry; Hacker, Michele; Koniares, Katherine; Yartel, Anthony; Adashi, Eli; Penzias, Alan (Fertility and sterility, 2024)
To examine whether the (1) scope of state-mandated insurance coverage for assisted reproductive technology (ART) and (2) proportion of the population eligible for this coverage are associated with reductions in racial/ethnic inequities in ART utilization. National cross-sectional, ecologic study. We employed estimates from the US Census Bureau of all women 20–44 years of age living in the US in 2018. Data on the number of women who initiated an ART cycle during that year that were reported to the US Centers for Disease Control and Prevention were obtained from the National ART Surveillance System. State mandates were classified according to the scope of required coverage for fertility services: Comprehensive, Limited, and No Mandate. Race and ethnic-specific ART utilization rates, defined as the number of women undergoing ≥1 ART cycles per 10,000 women, were the primary outcomes. As state mandates do not apply to all insurance plans, Comprehensive Mandate utilization rates were recalculated using denominators corrected for the estimated proportions of populations eligible for coverage. Across all mandate categories, Non-Hispanic (NH) Asian and NH White populations had the highest ART utilization rates, whereas the lowest rates were among Hispanic, NH Black, and NH Other/Multiple Races populations. Compared with the NH Asian reference group, the NH Black population had smaller inequities in the Comprehensive Mandate group than the No Mandate group (rate ratio [RR 0.33 [0.28–0.38] vs. RR 0.23 [0.22–0.24]). Using the Comprehensive Mandate group for each race/ethnicity as the reference, the NH Black and NH Other/Multiple Races populations showed the largest relative differences in utilization between the No Mandate and Comprehensive Mandate groups (RR 0.39 [0.37–0.41] and 0.33 [0.28–0.38], respectively). Within the Comprehensive Mandate group, the disparities in the Hispanic and NH Black populations moved toward the null after correcting for state-mandated insurance eligibility. Racial/ethnic inequities in ART utilization were reduced in states with comprehensive infertility coverage mandates. Inequities were further attenuated after correcting for mandate eligibility. Mandates alone, however, were not sufficient to eliminate disparities. These findings can inform future strategies aimed at improving ART access under a social justice framework. Seguro exigido por el Estado e inequidades raciales y étnicas en la utilización de tecnologías de reproducción asistida. Examinar si el (1) alcance de la cobertura del seguro exigido por el Estado para tecnología de reproducción asistida (ART) y (2) la proporción de la población elegible para esta cobertura están asociadas con reducciones en la inequidad racial/étnica en la utilización de ART. Estudio ecológico, transversal nacional. Empleamos estimaciones del Departamento de Censo de EEUU de todas las mujeres 20-44 años de edad que vivían en EEUU en 2018. Datos del número de mujeres que iniciaron un ciclo de ART durante ese año que fue reportado a los Centros de Control y Prevención de Enfermedades de EEUU fueron obtenidos del Sistema Nacional de Vigilancia de ART. Los mandatos del Estado fueron clasificados de acuerdo al alcance de cobertura requerida para servicios de fertilidad: Completo, Limitado y sin Mandato. Las tasas de raza y etnia específica en la utilización de ART, definidas como el número de mujeres sometidas a ciclos de ART por cada 10,000 mujeres, fueron los principales resultados. Como los mandatos estatales no aplican para todos los planes de seguro, las tasas de utilización del Mandato Completo fueron recalculadas utilizando denominadores corregidos para las proporciones de población estimadas eligibles para cobertura. En todas las categorías de mandato, las poblaciones No hispanas (NH) asiáticas y NH blancas tuvieron las tasas más altas de utilización de ART, mientras que las tasas más bajas fueron entre poblaciones Hispanas, NH negras, y NH Otras/Múltiples razas. Comparado con el grupo de referencia de NH asiáticas, la población de NH negras tuvo menores inequidades en el grupo de Mandato Completo que el grupo de No Mandato (relación de tasas [RR 0.33 [0.28–0.38] vs. RR 0.23 [0.22–0.24]). Usando el grupo the Mandato Completo para cada raza/etnicidad como la referencia, las poblaciones NH negras y NH otras/múltiple razas mostraron la mayor diferencia relativa en la utilización entre los grupos Sin Mandato y Mandato Completo (RR 0.39 [0.37–0.41] y 0.33 [0.28–0.38], respectivamente). Dentro del grupo de Mandato Completo, las disparidades en las poblaciones hispanas y NH negras se movieron hacia la nulidad luego de corregir la elegibilidad para el seguro exigido por el Estado. Las inequidades raciales/étnicas en la utilización de ART fueron reducidas en los estados con cobertura completa de infertilidad. Las inequidades se fueron atenuando luego de corregir el mandato de elegibilidad. Sin embargo, los mandatos por sí solos no fueron suficientes para eliminar las disparidades. Estos hallazgos pueden informar estrategias futuras destinadas a mejorar el acceso a ART bajo un marco de justicia social.